ANALISIS ASUHAN KEPERAWATAN MELALUI INTERVENSI WATER TEPID SPONGE PADA ANAK DENGAN HIPERTERMIA DI RSU UKI JAKARTA - Yesica Damayanti Manalu; Rizqi Nursasmita (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is an acute infectious disease caused by the Dengue virus which enters the body through the bite of the Aedes aegypti mosquito. The nursing problem that arises in children with DHF is hyperthermia. Hyperthermia is an increase in body temperature to be higher than usual. The child's normal body temperature is at 37.5oC, if the body shows this figure it indicates a fever caused by infection. The negative impact that can be caused if a child's fever is not handled properly and further treatment will cause dehydration due to increased evaporation of fluids so that the body can lack fluids. If fever is not treated quickly and appropriately, fever can endanger the safety of the child so that it can cause other complications (seizures and loss of consciousness). One of the nursing actions that can be performed on children with hyperthermia is a water tepid sponge. Water tepid sponge is an act of warm compresses with the technique of wiping given to patients who have high fever to reduce or reduce body temperature. Objective: To analyze nursing care through water tepid sponge intervention with ineffective hyperthermia problems with a children diagnosis of DHF. Result: The results of the nursing evaluation on the main nursing problem of hyperthermia based on progress notes, after the intervention of the water tepid sponge on children. A and children. D for 3 days with a frequency of 1 time per day obtained data on the third day of nursing action, namely that both clients experienced a decrease in body temperature. Body temperature children. A 38oC, after being given water tepid sponge therapy for 3 days it decreased to 36.7oC. body temperature children. D 39oC, after being given water tepid sponge therapy for 3 days it dropped to 37oC. Conclusion: Giving water tepid sponge intervention can overcome the problem of nursing hyperthermia as evidenced by a decrease in body temperature in children. Keywords: DHF, hyperthermia, water tepid sponge